Seed conditioning as an effective method to alleviate imbibitional injury in some leguminous crop seeds - S.K. JAIN; KALYANI SRINIVASAN; A.D. SHARMA (Seed Research, 2026)
Seeds in some leguminous crops viz, broadbean, chickpea (Brown), chickpea (Cream), cowpea, greengram, lentil and soybean conditioned to 9, 6 and 4% moisture contents were subjected to standard germination test. Results showed that cowpea and broadbean seeds were most susceptible to imbibitional injury. Soaking of these seeds in water for 16-20 hr prior to standard germination test resulted in a greater proportion of seeds failing to germinate, the degree of imbibitional injury being maximum in cowpea followed by broadbean. Seed conditioning (Slow rehydration) of these seeds to 17-21% moisture content was effective to mitigate the imbibitional damage. It is evident from the above study that the damage to the seeds following desiccation is more likely to be a consequence of imbibitional damage to which the seeds are more susceptible rather than a consequence of desiccation per se. The imbibitional damage can be mitigated to a large extent by slow conditioning of these legume seeds.